Utilization of digital health to improve self-management in patients with type 2 diabetes mellitus in the community: A literature review - Yaumil Hafsani Siregar (Journal of Community Nursing and Primary Care, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease that requires continuous self-management. Conventional community-based education is often limited by time, distance, follow-up intensity, and patients’ access to repeated counseling. Digital health offers an opportunity to strengthen diabetes self-management. Objective: This literature review aimed to synthesize evidence on the utilization of digital health to improve self-management among patients with T2DM in community settings. Methods: A literature review was conducted following the PRISMA 2020 reporting framework. Searches were conducted in PubMed and Google Scholar for articles published between 2022 and 2025 using combinations of “digital health,” “mHealth,” “mobile health,” “self-management,” “type 2 diabetes mellitus,” “community,” “education,” and “nursing.” After screening titles, abstracts, and full texts against predefined inclusion and exclusion criteria, seven articles were included in the final synthesis. Results: The seven included studies showed that digital health interventions, including mHealth, mobile applications, digital-based education, E-DIMAS, telehealth, and smartphone-supported education, were associated with improvements in knowledge, medication adherence, glycemic control, self-monitoring of blood glucose, dietary behavior, physical activity, diabetes self-care skills, and quality of life. Interventions with reminder features, interactive education, self-monitoring support, feedback, and follow-up by health professionals appeared to provide stronger support for sustained self-management behavior. Conclusion: Digital health is a promising strategy to improve self-management among patients with T2DM in community settings. Community nurses can integrate digital education, medication reminders, remote glucose monitoring, online dietary counseling, and scheduled follow-up into routine diabetes care.